Desarrollo de la planeación estratégica para agrofrutales Injertos 2022 – 2026 - Lizarazo Chanfelan, Leidy Yohana; Benitez Pedreros, Geraldine (Universidad Antonio Nariño, 2022)
The elaboration of a strategic plan for Agrofrutales Injertos is of great value, since that seeks to contribute to the company an overview of the organizational structure, in addition to allows to identify the strategies and tools that will allow in the future that the company is established and consolidated in the market, improving its levels of competitiveness and cost effectiveness.